Does inequality harm income mobility and growth? An assessment of the growth impact of income and education inequality in Paraguay 1992-2002 - Thomas Otter (Georg-August-Universität Göttingen, Ibero-America Institute for Economic Research (IAI), 2009)
Latin America is the most unequal region of the world in terms of income or expenditure, as well as regarding other aspects of economic or social exclusion. The region suffered the lost decade of the nineteen eighties, and experienced a modest recovery in the nineteen nineties. In the nineteen nineties, most of the governments implemented stabilization politics, more or less close to the proposals of the Washington Consensus. Paraguay itself, however, neither suffered a debt crisis nor a mayor economic instability during the eighties, so the stabilization policies would not have been necessary or useful for the Paraguayan economy and business cycles in the nineties. Nevertheless, many of the macroeconomic policies applied in Paraguay during the nineties were close to the Washington Consensus. The most striking macroeconomic result of the decade was a per capita income decrease beginning in late 1995, hand in hand with a poverty increase after 1996. Given the persistently high levels of poverty incidence in Paraguay to date, understanding the determinants of growth at the household level in Paraguayan economy remains an important but under-researched field in economics. This appears to be particularly true for the question whether inequality has a positive or negative effect on economic growth, a question that is both fundamental in (development) economics and highly relevant for poverty reduction policies. Although the effect of inequality on growth has important implications for poverty (Bourguignon, 2004; Ravallion, 1997), empirical evidence on this link is virtually inexistent for Paraguay.
Keywords: 330; Soziale Ungleichheit; Soziale Mobilität; Bildungschancen; Wirtschaftswachstum; Paraguay